Modifications and testing of KAU arecanut de-husker - RAJMOHAN C. K; Er. Jippu Jacob (Guide) (Tavanur 1996 Kelappaji College of Agricultural Engineering and Technology)
Arecanut palm is an extensively cultivated tropical palm, the nuts of which form a popular masticatory in India, the Middle-East and the Far-East. to evaluate the properties of arecanut relevant to dehusking. modification of KAU arecanut dehusker. to evaluate its performance
Modifications and testing of KAU arecanut de-husker